2019
DOI: 10.3748/wjg.v25.i33.4985
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir is a more suitable treatment than entecavir for chronic hepatitis B patients carrying naturally occurring rtM204I mutations

Abstract: BACKGROUNDHepatitis B virus (HBV) DNA polymerase mutations usually occur to long term use of nucleos(t)ide analogues (NAs), but they can occur spontaneously in treatment-naïve chronic hepatitis B (CHB) patients. The naturally occurring HBV DNA polymerase mutations might complicate antiviral therapy with NAs, leading to the generation of drug-resistant viral mutants and disease progression. The most common substitutions are known to be YMDD-motif mutations, but their prevalence and the influence on antiviral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Indeed, our previous study using a cohort of treatment-naïve patients with chronic HBV infection revealed a higher prevalence of naturally occurring NAr mutations in Korea compared to other areas, including China ( Kim et al, 2017 ). Our previous LNA-based RT–PCR assay also showed a higher prevalence of rt204I region YMDD variants, particularly in Korean HCC patients ( Choe et al, 2019 ). Higher rates of relapse in Korean chronic HBV infection patients with HBeAg seroconversion after lamivudine treatment have also been found, supporting the above hypothesis ( Song et al, 2000 ).…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, our previous study using a cohort of treatment-naïve patients with chronic HBV infection revealed a higher prevalence of naturally occurring NAr mutations in Korea compared to other areas, including China ( Kim et al, 2017 ). Our previous LNA-based RT–PCR assay also showed a higher prevalence of rt204I region YMDD variants, particularly in Korean HCC patients ( Choe et al, 2019 ). Higher rates of relapse in Korean chronic HBV infection patients with HBeAg seroconversion after lamivudine treatment have also been found, supporting the above hypothesis ( Song et al, 2000 ).…”
Section: Discussionmentioning
confidence: 71%
“…22 Another South Korean study demonstrated that TDF achieved significantly more complete viral response in rtM2041 variants than ETV treatment. 23 Adherence to treatment protocol was strictly supervised; hence the poor response to ETV as compared with tenofovir among HBeAg-positive patients could be attributable for some unknown reasons. HBV genotyping with mutation analysis are needed to accredit the better efficacy of TDF over ETV in HBeAg-positive CHB patients.…”
Section: Discussionmentioning
confidence: 99%